Dynamic Study on Fall Accidents and its Prevention: An Approach through Questionnaire Survey - S. Dhinu Priya, V. Nandhini, V. Santha Rubini, S. Manoj, D. Ambika, G. Poovizhi (International Journal of Advanced Science and Technology, 2020)
Workers working in the high-rise building suffer from work-related injuries and fatalities by falling from heights. Identifying the factors causing fall accidents and identifying the available fall protection systems in the construction sites. Most of the workers not wearing the fall harness belt mainly due to lack of awareness and due to the discomfort of the strap. The article shows fall frequency and factors causing the fall accidents and the existing fall protection methods in the construction sites. By increasing the safety in the construction can improve productivity and reduce the cost spent on compensation and fee spent on health.